Tipe Urban Sprawl dan Eksistensi Pertanian di Wilayah Pinggiran Kota Denpasar - Putu Indra Christiawan (Department of Urban and Regional Planning, Diponegoro University, 2019)
Denpasar City as the capital of Bali Province is attractive to regional development. The limited space of Denpasar City directs the development towards the periphery. The extension of physical urban form will be a significant factor of suburban developments. The study aims to examine the type of urban sprawl development in the Denpasar suburbs, and their relation to the existence of agriculture. The qualitative research method is used to analyze the type of urban sprawl with the following indicators of typical land uses covering rice fields, forest park, open land, and settlements. Remote sensing analysis of these four indicators applies GIS model drawn from three time-series data of 2005, 2010 and 2015. Spatial approaches are applied to examine the patterns and structures of urban sprawl types. The results find two main types of urban sprawl development in the city suburbs, that is, leapfrog type which is mostly scattered in the north, and the ribbon type mainly centered in the eastern part of Denpasar City. Both types of urban sprawl play a crucial role in decreasing the amount of agricultural land, especially rice fields, in the suburbs of Denpasar.